Psychological profile of the leader and investment decision practice of the small and medium-sized enterprise (SME) in the context of the COVID-19 crisis in Ivory Coast - Bassife Ouattara (The Journal of Entrepreneurial Finance (JEF), 2022)
This article examines the different investment decision practices of the leader of small and medium-sized enterprises (SMEs) during the COVID-19 health crisis and highlights the influence of the leader's psychological profile on these practices. Thus, primary data was collected from the interview guide and questionnaires submitted to 112 executives. The results obtained through the tests indicate the existence of a direct link (significant influence) between certain psychological profiles of the leader and investment decision-making practices in times of crisis.
Keywords: 650; Crisis; psychological profile; investment decision-making practices; SME manager